Simulation of a pneumatic tube cutting station: A case study in developing a framework for discrete event simulation model maintainability - Hákonardóttir, Birta; Hedlund, Robert (My University, 2023)
Volvo GTO is a truck manufacturing company that offers high customisation and tailor-suited vehicles towards their customers. One of their processes entails the production of pneumatic tubes that supply an array of functions within a truck. The tube production is complex and has high variation. Therefore, the capacity of the tube cutting station cannot be determined statically. In this thesis, a discrete event simulation (DES) model is built for the tube cutting station to determine its capacity. The model will also be used to explore other model parameters. However, building a discrete event simulation model is a time consuming process and there fore, often costly for companies. In some cases, a model will be used more often than once and needs to be maintained over time to be of use. In this thesis, the subject of maintainability of DES is discussed and this project is used as a case study. Following this, two frameworks for maintainability are established. One for organ isational maintainability and another for technical maintainability. The technical maintainability framework highlights internal support that can be applied to the model, while the organisational framework refers to external support that can be applied to the model to support model maintainability. The framework is estab lished based on the results of a literature study and the authors’ observations made during the process of modelling the DES model of the tube cutting station. Both frameworks consists of several criteria that should support the upkeep of the DES model long term.
Keywords: Discrete Event Simulation, Maintenance, Maintainability Framework